Performance and Energy Consumption Analysis of Embedded Applications Based on Android Platform - Vieira, Andrws; Debastiani, Daniel; Agostini, Luciano; Marques, Felipe; Mattos, Julio C. B. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
This paper presents an analysis of embedded applications based on Android Platform. Analyzing performance and energy consumption from different algorithmic versions this work tries to find a performance and energy pattern for the paradigm used in each used algorithm. Thus, the developer can select the best algorithm version for each application based on the requirements. Android is a Linux based mobile operating system developed by Google in conjunction with the Open Handset Alliance. Nowadays, Android is the world's leading smartphone platform. The Android Platform provides a rich development environment (SDK) including an API, development and debug tool and so on. However, during the development process it is necessary to handle with the system functionalities and it must at the same time help the handling of the embedded systems tight constraints, like performance, energy and power. This paper shows some performance and energy consumption results for a set of applications using different algorithmic versions.